Active Safety Methodologies of Rail Transportation - Qin, Yong; Jia, Limin (Advances in High-speed Rail Technology, 2019)
Safe and high-efficiency operation are two main issues in rail transportation. This book focuses on these two key issues, bringing together a wealth of research to offer theoretical and technical support for rail operations and maintenance. In addition, it presents a comprehensive active safety assurance system for rail transportation, which includes the quantitative state identification and prediction of train components; rail transportation safety and reliability assessment methods; and rail transportation risk assessment at the rail networks level, which achieves the quantitative and high-precision monitoring of complex systems in real-time. In addition, it extends active safety based theory to safety prognostic analysis in the traffic system. Lastly, representative case studies verify that the theory is suitable for the actual traffic system.